1992
DOI: 10.1002/gcc.2870050411
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and loss of heterozygosity studies in ependymomas, pilocytic astrocytomas, and oligodendrogliomas

Abstract: Cytogenetic and/or loss of heterozygosity studies were performed on 13 ependymomas, 11 pilocytic astrocytomas, and 18 oligodendrogliomas. Loss of chromosome 22 was the most frequent genetic abnormality among the ependymomas. We found no consistent genetic abnormality in pilocytic astrocytomas. The most common genetic abnormality in oligodendrogliomas was loss of a portion of chromosome 19. Each informative oligodendroglioma had loss of alleles mapped to the long arm (q) of chromosome 19. One oligodendroglioma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(94 citation statements)
references
References 30 publications
(43 reference statements)
10
83
0
1
Order By: Relevance
“…The corollary of this is that low-grade tumours, which in practice are easier to treat, have more widespread abnormalities than the high-grade tumours, a situation that also pertains to neuroblastomas (Plantaz et al, 1997). Loss of 22q has been the commonest abnormality in several genetic studies of ependymoma (Ransom et al, 1992;Mazewski et al, 1999;Vagner-Capodano et al, 1999), though gain of 1q or loss of 6q assumes predominance in others (Reardon et al, 1999;Ward et al, 2001). If the changes suggestive of intermediate ploidy are discounted, loss of 22q is the most frequent genetic abnormality in our series of ependymomas, occurring in 26% of ependymomas, which is in line with data from other CGH studies (Reardon et al, 1999;Hirose et al, 2001;Ward et al, 2001).…”
Section: Genetics and Genomicssupporting
confidence: 89%
See 1 more Smart Citation
“…The corollary of this is that low-grade tumours, which in practice are easier to treat, have more widespread abnormalities than the high-grade tumours, a situation that also pertains to neuroblastomas (Plantaz et al, 1997). Loss of 22q has been the commonest abnormality in several genetic studies of ependymoma (Ransom et al, 1992;Mazewski et al, 1999;Vagner-Capodano et al, 1999), though gain of 1q or loss of 6q assumes predominance in others (Reardon et al, 1999;Ward et al, 2001). If the changes suggestive of intermediate ploidy are discounted, loss of 22q is the most frequent genetic abnormality in our series of ependymomas, occurring in 26% of ependymomas, which is in line with data from other CGH studies (Reardon et al, 1999;Hirose et al, 2001;Ward et al, 2001).…”
Section: Genetics and Genomicssupporting
confidence: 89%
“…If the changes suggestive of intermediate ploidy are discounted, loss of 22q is the most frequent genetic abnormality in our series of ependymomas, occurring in 26% of ependymomas, which is in line with data from other CGH studies (Reardon et al, 1999;Hirose et al, 2001;Ward et al, 2001). However, the frequency of loss of 22q in ependymomas varies greatly (up to 71%) in previous studies that have used a variety of methods (Ransom et al, 1992;Neumann et al, 1993;Kramer et al, 1998;Vagner-Capodano et al, 1999;Zheng et al, 2000). This variability is likely to reflect ascertainment bias, because the frequency of loss of 22 in ependymomas varies according to histological variant, anatomic site, and age of the patient.…”
Section: Genetics and Genomicssupporting
confidence: 89%
“…Additionally, a germ-line mutation of exon 7 of the p53 gene, the most commonregion of mutation in patients with the Li-Fraumeni cancer syndrome, has been reported in one patient with a malignant ependymoma of the posterior fossa in childhood ( 17). Chromosomal abnormalities involving chromosome 9, 20 or 1 1 have also been reported in patients with ependymomas (9). Finally, translocations containing chromosome 1 1q13: t (l l ; 17)(ql3; q21) and t(10; ll; 15)(pl2.2; ql3; pl2) have been reported in two patients with childhood supratentorial ependymoma (10, 1 1).…”
Section: Discussionmentioning
confidence: 90%
“…Karyotypic analysis of solid tumors has demonstrated that Ilql3 is a relatively frequent site of chromosome breakage (8). Several patients with chromosome1 Iql 3 abnormalities have also been diagnosed with ependymomas (9), and translocations containing chromosome1 lql 3 have been reported in two patients with childhood supratentorial ependymoma ( 1 0, 1 1 ). These chromosome abnormalities have been suspected to play a role in the pathogenesis of ependymoma.…”
Section: Introductionmentioning
confidence: 99%
“…In their most malignant and prevalent form these tumors are classi®ed as glioblastoma multiforme (GBMs) with an average patient survival of approximately 1 year. The vast majority of GBM examined by either karyotypic or molecular analyses have shown a multiplicity of chromosomal aberrations including ampli®cation of chromosome 7, and regional deletions or monosomies of chromosomes 9p21, 10p, 10q, 11p15, 13q13, 17p13, 19, and 22 (Bigner et al, 1988;Fults et al, 1989Fults et al, , 1990James et al, 1988James et al, , 1991Rasheed et al, 1992Rasheed et al, , 1995Ransom et al, 1992;Ritland et al, 1995). The most common chromosomal alteration involves an apparent grade-speci®c loss of chromosome 10 alleles associated with high grade GBMs.…”
Section: Introductionmentioning
confidence: 99%